“For a long time the Peruvian oppressed…”: A historical approach on the inclusion of the apocryphal stanza in the National Anthem of Peru, contained in the Ayacucho Album of 1862 - Irrazabal Laos, Korina (2024)
The succession of a colonial state to an independent one meant a vast path that gradually took shape until the beginning of the 20th century. With this objective, it was necessary to promote national awareness in the collective imagination. In this sense, national anthems played a very important symbolic role in the establishment of all Latin American nations. Unlike other patriotic symbols, such as coats of arms or flags, these have the capacity to achieve much greater effects of belonging among the population, legitimizing the commitment to the causes for which they fought, due to their predominantly discursive nature. Among these resources, national anthems occupy a place little explored by researchers.